Profiling unmanned aerial vehicle photography tourists. Issue 14 (17th July 2020) - Chen, Xiliang; Li, Gang; Yang, Lan; Nie, Qifan; Ye, Xinyue; Liang, Yanjun; Xu, Tingting
ABSTRACT: Based on User Generated Content (UGC) data, namely Unmanned Aerial Vehicle (UAV) photos and corresponding social media captions, this paper uses the methods of AI cognitive analysis and GIS spatial analysis to profile UAV photography tourists. The findings of this study reveal that UAV photography tourists primarily take pictures of natural landscapes, most of which do not contain humans, concentrated in the coastal regions. Additionally, a sentiment analysis indicates that tourists' opinions of photography are typically positive.